Is there really an eccentric action of the hamstrings during the swing phase of high-speed running? part I: A critical review of the literature. Issue 23 (2nd December 2017) - Van Hooren, Bas; Bosch, Frans
ABSTRACT: It is widely assumed that there is an eccentric hamstring muscle fibre action during the swing phase of high-speed running. However, animal and modelling studies in humans show that the increasing distance between musculotendinous attachment points during forward swing is primarily due to passive lengthening associated with the take-up of muscle slack. Later in the swing phase, the contractile element (CE) maintains a near isometric action while the series elastic (tendinous) element first stretches as the knee extends, and then recoils causing the swing leg to forcefully retract prior to ground contact. Although modelling studies showed some active lengthening of the contractile (muscular) element during the mid-swing phase of high-speed running, we argue that the increasing distance between the attachment points should not be interpreted as an eccentric action of the CE due to the effects of muscle slack. Therefore, there may actually be no significant eccentric, but rather predominantly an isometric action of the hamstrings CE during the swing phase of high-speed running when the attachment points of the hamstrings are moving apart. Based on this, we propose that isometric rather than eccentric exercises are a more specific way of conditioning the hamstrings for high-speed running.